(untitled) (Journal of Information Technologies in Education (ITE), 2013)
Specifics of formation of professional competence for the students of an ecological profile (in a context of possession by modern technologies of information processings) is considered. The estimated themes and the content of some teaching sessions of a course «Information technologies» for students of specialty «Ecology and environmental protection» is offered.